Effect of the Surface Texture on Laser Joining of a Carbon Fiber-Reinforced Thermosetting Plastic and Stainless Steel - Sheng, L.Y.; Lai, C.; Xu, Z.; Jiao, J. (Проблемы прочности, 2019)
A carbon fiber-reinforced thermosetting plastic and stainless steel were joined by the fiber laser. The surface texture effect on the joint was investigated. The abrasive paper scratching is shown to form single directional striae on stainless steel with intermittent ridges. Laser texture processing creates uniformly distributed microdimples and ridges, which forms a rectangular cellular structure. This processing can improve the fluidity of molten polyphenylene sulfite during laser joining. Laser scanning on stainless steel results in the formation of fusion and heat-affected zones. In the heat-affected zone, lathy ferrite is located along the boundary, while in the fusion zone, ferrite forms the skeletal structure and separates austenite into a cellular structure. The surface texture modification can contribute to the adhesive strength between stainless steel and polyphenylene sulfite through on enlarged contact surface area by forming striae, microdimples, and ridges. As compared to the abrasive paper scratching, the stainless steel/plastic joint with laser texture processing exhibits a higher shear strength.